People's Republic of China : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the People's Republic of China. (IMF Staff Country Reports; Country Report ;, 2022)
China's recovery is well advanced-but it lacks balance and momentum has slowed, reflecting the rapid withdrawal of fiscal support, lagging consumption amid recurrent COVID-19 outbreaks despite a successful vaccination campaign, and slowing real estate investment following policy efforts to reduce leverage in the property sector. Regulatory measures targeting the technology sector, intended to enhance competition, consumer privacy, and data governance, have increased policy uncertainty. China's climate strategy has begun to take shape with the release of detailed action plans. Productivity growth is declining as decoupling pressures are increasing, while a stalling of key structural reforms and rebalancing are delaying the transition to "high-quality"-balanced, inclusive and green-growth.